The shapes of the rotation curves of star-forming galaxies over the last ≈10 Gyr. Issue 1 (13th February 2019) - Tiley, Alfred L; Swinbank, A M; Harrison, C M; Smail, Ian; Turner, O J; Schaller, M; Stott, J P; Sobral, D; Theuns, T; Sharples, R M; Gillman, S; Bower, R G; et al.
Abstract: We analyse maps of the spatially resolved nebular emission of ≈1500 star-forming galaxies at z ≈ 0.6–2.2 from deep K -band Multi-Object Spectrograph and MUSE observations to measure the average shape of their rotation curves. We use these to test claims for declining rotation curves at large radii in galaxies at z ≈ 1–2 that have been interpreted as evidence for an absence of dark matter. We show that the shape of the average rotation curves, and the extent to which they decline beyond their peak velocities, depends upon the normalization prescription used to construct the average curve. Normalizing in size by the galaxy stellar disc-scale length after accounting for seeing effects (R_d^′ ), we construct stacked position-velocity diagrams that trace the average galaxy rotation curve out to 6R_d^′ (≈13 kpc, on average). Combining these curves with average H i rotation curves for local systems, we investigate how the shapes of galaxy rotation curves evolve over ≈10 Gyr. The average rotation curve for galaxies binned in stellar mass, stellar surface mass density and/or redshift is approximately flat, or continues to rise, out to at least 6R_d^′ . We find a trend between the outer slopes of galaxies' rotation curves and their stellar mass surface densities, with the higher surface density systems exhibiting flatter rotation curves. Drawing comparisons with hydrodynamical simulations, we show that the average shapes of the rotation curves for our sample of massive, star-forming galaxies at z ≈ 0–2.2 are consistent with those expected from lambda cold dark matter theory and imply dark matter fractions within 6 R d of at least ≈60 per cent.